The Effectiveness of Aloe Vera Compresses in Reducing Body Temperature in Children with Fever Aged 6–12 Years - Yona Sari; Ariyanti Ariyanti; Tiara Fatrin (Indonesian Journal of Global Health Research, 2026)
Children need a strong immune system so they are not easily infected with viruses and bacteria that can cause fever. For this reason, optimal attention is needed so that it is not easily infected by viruses and bacteria. There are other alternatives. Apart from using pharmacological drugs to lower a child's body temperature, the process of giving aloe vera compresses can also reduce the child's body temperature. Preliminary studies found that there are still some children who cannot take pharmacological drugs. To overcome this problem, an innovation was created in the form of an aloe vera compress which is believed to be able to reduce the body temperature of children with fever because it contains lignin and saponin. The aim of this study was to identify differences in children's body temperature before and after intervention. This research used a quasi-experiment with a one group pre test - post test design. The population was 15 respondents with fever aged 6-12 years using accidental sampling. The results of the comparison test before and after (paired t-test) showed a significance value of 0.00 (<0.05). This shows that the aloe vera compress is effective in reducing the body temperature of feverish children aged 6-12 years. Based on the average (mean) body temperature before the intervention (pre test) it was found to be 38.480 and the average (mean) body temperature after the intervention (post test) was 37.833.